EVALUATION OF CLINICIAN SATISFACTION AND CLINICAL OUTCOMES WITH OPTICAL IMPRESSION SYSTEMS IN PROSTHETIC DENTISTRY - Sajid Ali Khan; Sheeba Wahab; Kamran khan; Muhammad Asif Nawaz; Yasir Ali Shah; Hijab Moeen (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: This study aimed to evaluate clinician satisfaction and clinical outcomes associated with optical impression systems compared to traditional impression methods in prosthetic dentistry.Methodology:The study used a prospective observational design with 230 participants. Data collection included demographic information, types of impression systems used, clinician satisfaction surveys assessing ease of use, accuracy, comfort, and overall satisfaction. It also involved clinical outcomes assessments such as impression accuracy and procedure time. Statistical analysis involved descriptive statistics, comparative analysis using chi-sqaure and t-tests to identify influencing factors.Results:The mean of the years of experience was 0.12 0.05. Additionally, 85% of clinicians reported high accuracy with optical system versus 70% with traditional methods. Furthermore, impressions taken using optical systems exhibited greater accuracy (p = 0.034).Conclusions: This study highlights the benefits of using optical impression systems in prosthetic dentistry, including greater clinician satisfaction, improved clinical outcomes, and enhanced accuracy and efficiency, which could improve prosthetic dental practice.